Interferon-α coincides with suppressed levels of pentraxin-3 (PTX3) in systemic lupus erythematosus and regulates leucocyte PTX3 in vitro. (31st March 2017) - Wirestam, L; Enocsson, H; Skogh, T; Eloranta, M L; Rönnblom, L; Sjöwall, C; Wetterö, J
Summary: Dysfunctional elimination of cell debris, and the role of opsonins such as pentraxins, is of interest regarding systemic lupus erythematosus (SLE) pathogenesis. Interferon (IFN)-α is typically elevated during SLE flares, and inhibits hepatocyte production of the pentraxin 'C-reactive protein' (CRP), partly explaining the poor correlation between CRP levels and SLE disease activity. The extrahepatically produced 'pentraxin 3' (PTX3) shares waste disposal functions with CRP, but has not been studied extensively in SLE. We analysed serum PTX3 in SLE, and assessed its interference with IFN-α in vitro . Serum samples from 243 patients with SLE and 100 blood donors were analysed regarding PTX3. Patient sera were analysed for IFN-α, and genotyped for three PTX3 single nucleotide polymorphisms reported previously to associate with PTX3 levels. Stimulated PTX3 release was assessed in the presence or absence of IFN-α in blood donor neutrophils and peripheral blood mononuclear cells (PBMC). Serum PTX3 was 44% lower in patients with SLE compared to blood donors ( P < 0·0001) and correlated with leucocyte variables. Patients with undetectable IFN-α had 29% higher median PTX3 level than patients with detectable IFN-α ( P = 0·01). PTX3 production by PBMC was inhibited by IFN-α, whereas neutrophil degranulation of PTX3 was increased. No differences in PTX3 levels were observed between the SNPs. In conclusion, median serum PTX3 is lower in SLE (especially when IFN-α is detectable) compared to blood donors. In addition to its potential consumption during waste disposal, it is plausible that IFN-α also attenuates PTX3 by inhibiting synthesis by PBMC and/or exhausting PTX3 storage in neutrophil granules. Graphical Abstract: